Analisis Tingkat Pemahaman Konsep Sains Mahasiswa Calon Guru Sekolah Dasar - Hasnawati Hasnawati; Muhammad Syazali; Arif Widodo (Postgraduate, University of Mataram, 2022)
Understanding the concept is one of the most important parts of realizing a teacher's professional competence. As elementary school teacher candidates, Elementary School Teacher Education students must have good conceptual understanding skills to realize the expected professional competence. This study aims to analyze elementary school teacher candidates' level of understanding of science concepts, specifically on temperature and heat, electricity, magnetic fields, and the solar system. This type of research is quantitative descriptive with research subjects of Elementary School Teacher Education Study Program students who program elementary science education courses. The total sample of 218 was selected by purposive sampling. Data on understanding the science concepts of elementary school teacher candidates were collected using a three-level test instrument equipped with a Certain Response Index (CRI). Results of data analysis showed that 46.27% understood the concept well, 9.04% understood the concept but were unsure, 30.90% had misconceptions and 13.67% did not know the concept. The data illustrates that the number of elementary school teacher candidates who experience misconceptions is still quite high. The causes of misconceptions among students in understanding science concepts include material that is abstract, complex, has many mathematical equations and contains many images that are difficult to explain physically. Based on the results of this study, it is necessary to provide positive feedback and improve learning to facilitate elementary school teacher candidates so that they can understand science concepts easily and correctly.